Where now for infection services in the NHS? How lessons from the pandemic should drive long-overdue integration of microbiology and infectious diseases. Issue 6 (2022) - Llewelyn, Martin J; Price, Nicholas; Ratnaraja, Natasha; Atkins, Bridget; Partridge, David; Jeffery, Katie
No abstract available